Proceedings of 21th International Drying Symposium 2018
DOI: 10.4995/ids2018.2018.7405
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying of soymilk: evaluation of process yield and product quality

Abstract: The aim of this work was to evaluate the effect of inlet air temperature and gum Arabic concentration on yield of spray drying of soymilk and powder quality (moisture content, water activity and antioxidant capacity). Since soymilk had a significant lipid content, gum Arabic played a significant role as an emulsion stabilizer, improving process yield and preserving antioxidant capacity. However, temperature did not affect antioxidant capacity. The optimal condition to obtain higher antioxidant capacity was: 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The images showed that PEF processing reduced the particle size and uniformity. Finally, SEM has also been utilized to characterize the microstructure of powders produced by spray drying soymilk (Olmos et al, 2018).…”
Section: Practical Examples Of Utilizationmentioning
confidence: 99%
“…The images showed that PEF processing reduced the particle size and uniformity. Finally, SEM has also been utilized to characterize the microstructure of powders produced by spray drying soymilk (Olmos et al, 2018).…”
Section: Practical Examples Of Utilizationmentioning
confidence: 99%